Narodowy geniusz, czyli portret Fryderyka Chopina w Ostatnim koncercie Stanisławy Fleszarowej-Muskat - Olszewska, Maria Jolanta (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The drama Ostatni koncert (The Last Concert) (1960) by Stanisława Fleszarowa-Muskat, originally written as a radio play, sits on the border between popular and fictional literature. The text was intended for a wide audience. The plot focuses on a single event – Frédéric Chopin’s last concert in Warsaw, just before his departure to France, which took place on October 11, 1830. Youth, as it was understood by the romantics, turns out to be a time that shaped Chopin’s artistic personality. In this drama, the independence background is important as it highlights Chopin’s ties to the fate of his homeland, which gives his music a patriotic and revolutionary dimension. In sounds, Chopin’s brilliant music expresses the essence of the Polish soul: its nobility and love of freedom. Chopin’s concert took place at a turning point both for the composer and for the nation whose spirit he expressed through sounds. The drama about Chopin, the national genius, is at the same time a drama about a national community that acquires its identity by identifying with his music.